Pengembangan Sistem Informasi Aset Fisik Masjid (Studi Kasus: Masjid Ibnu Sina Jl. Veteran Malang) - Rayhan Adri; Ismiarta Aknuranda; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Ibnu Sina Mosque, located in Malang City, has a mosque management organization which consist of takmir and remaja masjid that aims to build a mosque that is comfortable for the community to use. Many activities carried out by mosque management organization are related to routine worship activities and spiritual activities that require physical assets to support them. However, there is a problem with the information on assets owned by the mosque which could potentially cause obstruction of mosque activities due to unknown asset conditions. The absence of information on mosque assets can also lead to waste because the proposed purchase of goods is not managed so that it can lead to repurchasing of items already owned by the mosque. Based Ibnu Sina Mosque's problems on asset information, this study aims to build a physical asset information system that can facilitate mosque management in managing assets owned by the mosque. With the physical asset information system, it is hoped that the mosque management can use the information system to implement better mosque physical asset management. The physical asset information system developed with waterfall approach on web-based system with Laravel framework that based on PHP programming laguange to facilitate easier access and further development of the information system of the Ibnu Sina Mosque. The results of the validation test on the physical asset information system of the Ibnu Sina Mosque give good results with some feedback records from users and the compatibility test results show good compatibility on most web browsers available for the desktop version.